Comparison of quality of dry turmeric (Curcuma longa) produced by slicing and other curing methods - R Rakhi, E Jayashree, T J Zachariah, (Journal of Spices and Aromatic Crops, 2019)
The study determines the effect of slicing and curing turmeric (var. Alleppey Supreme) on the quality of dry turmeric rhizomes produced. The turmeric rhizomes were sliced to 5 mm and the curing methods followed were steam curing in TNAU model turmeric boiler for 60 min and traditional water boiling for 60 min. The drying characteristics curves obtained indicated that the time required for drying was significantly reduced by slicing to 127 h (5 days) and the maximum time of 288 h (12 days) was required for complete drying of steam cured turmeric in TNAU boiler. Quality analysis of the dried turmeric samples indicated that the maximum retention of primary metabolites i.e. carbohydrates, proteins, fat and starch was found in turmeric samples cured by water boiling method for 60 min corresponding to 53.15, 3.16, 2.72 and 49.14%, respectively and the maximum retention of secondary metabolites i.e. essential oil, oleoresin and curcumin content were observed in sliced samples and the values corresponded to 6.23, 10.51 and 3.74%, respectively.